Exploring Information Seeking Anxiety among Research Students in Khyber Pakhtunkhwa Universities (Journal of Social Sciences Review, 2024)
This study investigated information-seeking Anxiety (ISA) among postgraduate students in Khyber Pakhtunkhwa, Pakistan, using a sample of 367 students from three prestigious universities. Employing a correlational research design, the study utilized the Erfanmanesh Information Seeking Anxiety Scale and considered the Grand Point Average (GPA) for academic success. Data collection involved a standardized questionnaire, and statistical analyses included reliability checks and descriptive and inferential statistics. Results revealed a significant inverse relationship between emotional intelligence and information-seeking anxiety. The study emphasizes the importance of emotional intelligence in reducing information-seeking anxiety, suggesting implications for information literacy curricula and the potential for improvement through training and consultant interventions. The findings contribute to addressing information-seeking anxieties and enhancing emotional intelligence skills among postgraduate students, benefiting academia, psychologists, library practitioners, and information professionals.
Keywords: Information Seeking Anxiety; Library Anxiety; Correlation; Relationship; Research Students; University; Khyber Pakhtunkhwa; Pakistan